SMART PLS Analysis of Community Characteristics and Perceptions of Drug Buying Behavior through E-Commerce in the City of Blitar - Widhoretno Puspandari; Jason Merari Peranginangin; Lucia Vita Inandha Dewi (International Journal of Contemporary Sciences (IJCS), 2024)
This research aims to determine the relationship between community characteristics and community perceptions of online drug purchasing behavior via e-commerce. The research uses a quantitative sample with people living in Blitar City aged 16-50 years, who have experience purchasing using e-commerce. Data analysis using SmartPLS v.3. The results show that community characteristics and community perceptions of online drug purchasing behavior show a significant relationship